2018
DOI: 10.1093/ntr/nty012
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status and Survival Among a National Cohort of Lung and Colorectal Cancer Patients

Abstract: The results from our analysis of patients in the Cancer Care Outcomes Research and Surveillance (CanCORS) consortium, a large, geographically diverse cohort, show that both lung and colorectal cancer patients who were actively smoking at diagnosis have worse survival as compared to never smokers. While current smoking is detrimental to survival, cessation upon diagnosis may not mitigate this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
(76 reference statements)
2
12
0
3
Order By: Relevance
“…Overall, adults with a cancer diagnosis had lower rates of smoking and higher rates of quitting than adults without cancer, regardless of SUD status. Our estimate of smoking prevalence in patients with cancer (and without SUDs) is largely consistent with the most recent population-based estimate of adults with cancer using the National Health Interview Survey from 2017 (i.e., 13% prevalence), as well as other estimates of smoking prevalence from community-based samples (e.g., 14–15%) [ 10 , 19 , 20 , 21 ]. We also found a lower prevalence of SUDs in adults with versus without cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Overall, adults with a cancer diagnosis had lower rates of smoking and higher rates of quitting than adults without cancer, regardless of SUD status. Our estimate of smoking prevalence in patients with cancer (and without SUDs) is largely consistent with the most recent population-based estimate of adults with cancer using the National Health Interview Survey from 2017 (i.e., 13% prevalence), as well as other estimates of smoking prevalence from community-based samples (e.g., 14–15%) [ 10 , 19 , 20 , 21 ]. We also found a lower prevalence of SUDs in adults with versus without cancer.…”
Section: Discussionsupporting
confidence: 84%
“…However, the present study has several limitations. A previous study found that never-smokers had a lower mortality risk than current smokers (HR 0.79, 95% CI, 0.64 to 0.99) among CRC patients [ 34 ], but smoking status was not included in our analysis. Some treatments, such as surgery, chemotherapy, and radiotherapy, were also not included.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the smoker group included significantly younger patients (median age, 73 vs. 68 years, p = 0.009), which may have affected this result. The association between smoking status and survival in patients with colorectal cancer has yet to be established, with most [22][23][24][25] but not all studies [26][27][28], linking cigarette smoking to worse survival rates.…”
Section: Discussionmentioning
confidence: 99%